PENURUNAN TEKANAN DARAH PADA PASIEN HIPERTENSI BERBASIS TERAPI PIJAT REFLEKSI KAKI - Chanif -; Khoiriyah - (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Hypertension or high blood pressure is a vascular disorder that results in the supply of oxygen and nutrients carried by the blood to the tissues of the body is inhibited. Hypertension is a major cause of heart failure, stroke, kidney failure. About 20% of the adult population has hypertension, over 90% of them suffer from primary hypertension. Several factors can cause hypertension are lifestyle with the wrong diet, gender, physical exercise, food, stimulants (substances that speed up the body's functions) as well as stress. A wide variety of relaxation techniques already developed one of which is to provide therapeutic foot reflexology.The purpose of this study was to analyze the effectiveness of foot reflexology massage therapy on blood pressure in hypertensive patients in Semarang. The design used in this research is the "Quasi-experimental design in two groups using a foot reflexology massage therapy in intervention group. The number of samples in this study is adult patients with primary hypertension were male sex as many as 11 patients each group.Based on the test results of pair t-test showed that there were significant differences in systolic blood pressure, diastolic and MAP on the treatment before and after administration of therapeutic foot reflexology for 30 minutes (p value = 0:00). The hipothesis test betwen two groups using independent t-test showed that there was significant differences in systolik, diastolic and MAP blood pressure betwen intervention and control group (p value = 0:00). This study recommended to patients and families, especially in the treatment of hypertensive patients in the home to prevent the complications of hypertension. Keywords ; hypertension, foot reflexology massage, blood pressure